Catostemma lanceolatum (Malvaceae/Bombacoideae/Adansonieae), a new species from the Brazilian Amazon - Ferreira, Carlos D. M.; Alverson, William S.; Demarchi, Layon O.; Bovini, Massimo G.; Baumgratz, José F. A. (Phytotaxa, 2023)
We describe Catostemma lanceolatum, a new species endemic to the Brazilian Amazon, which at present is known only in the state of Amazonas. This new taxon is similar to C. altsonii, mainly by the length of its pedicels, but can be distinguished by the shape of its leaflets, the shape and size of the bracteoles, size of its hypanthium, number of calyx lobes, and the number and length of its filaments. We present a morphological description, taxonomic comments, an illustration, a distribution map, an assessment of its conservation status, and a comparative analysis of the new species and C. altsonii, the most morphologically similar species.